PENERAPAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN MENYANYIKAN LAGU DAERAH RIAU SISWA KELAS V SDN 40 PEKANBARU - Sri Alam, Dayangku Mustika Sri Alam Mustika; Antosa, Zariul Antosa Zariul; Noviana, Eddy Noviana Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The appointed issues in this research is to increased student ability to sing a folk song Riau province on fifth grade student of SDN 40 Pekanbaru, with use drill method. The music lesson in this school only give material lesson or lecture method, their never ask the student to practice this caused by lack of knowledge from the music’s teacher. In music lesson only give lecture method, its make the student passive, so that, the formulation of this problem is whether the application of drill method can increased the student ability to sing a folk song Riau Province on fifth grade’s student SDN 40 Pekanbaru the subject of this research is 33’s fifth grade student SDN 40 Pekanbaru, on year book 2013/2014. This research have two cycle have three meeting and one final research. Instrument of data collection in this research are teacher’s observation sheets, student’s observation sheets assessment sheets. This called Penelitian Tindakan Kelas (PTK)’’. The result of this research shows that’s drill method can increased student ability to sing a folk song Riau Province, in the beginning, the student’s average value increased to 68, then in second cycle, the student’s average value increased to 75. It shows that application drill method can increased student ability to sing a folk song Riau Province on fifth grade student SDN 40 Pekanbaru.Keywords :Drill methode, ability to sing a folk song Riau Province